Painting the cannon's roar : music, the visual arts and the rise of an attentive public in the age of Haydn, c.1750 to c.1810 /: music, the visual arts and the rise of an attentive public in the age of Haydn, c.1750 to c.1810. (2017) - Tolley, Thomas
No abstract available